Synthesis of Mesoporous Silica from Beach Sand by Sol-Gel Method as a Ni Supported Catalyst for Hydrocracking of Waste Cooking Oil - Siti Salamah; Wega Trisunaryanti; Indriana Kartini; Suryo Purwono (Universitas Gadjah Mada, 2022)
Mesoporous silica (MS) supported by nickel was synthesized from Parangtritis beach sand and assessed for its activity and selectivity as catalysts in hydrocracking waste cooking oil into biofuel. The synthesis of MS was done by the sol-gel method. Ni/MS catalysts using Ni weight variations of 1, 5, and 10 wt.% were denoted as Ni/MS1, Ni/MS5, and Ni/MS10 and were compared to standard mesoporous silica (Ni/SBA-15). The catalysts were characterized using FTIR, XRD analysis, N2 gas sorption analysis, SEM-EDX, and TEM. Catalyst Ni/MS1, Ni/MS5, Ni/MS10, and Ni/SBA-15 have specific surface areas of 130.5, 195.9, 203.9, and 381.2 m2/g and the average pores of 12.30, 9.80, 11.12, and 8.70 nm, respectively. The hydrocracking was run four times to evaluate the catalyst reusability. The hydrocracking WCO has 95.8, 82.4, and 85.2%, respectively. While Liquid fractions produced were 38.8, 43.2, and 50.2 wt.%, each of which contains gasoline of 37.09, 39.76, and 44.27 wt.%, Ni/MS10 has the highest liquid products of 50.2 wt.% and was selective to gasoline fractions up to 44.27%. Therefore, the catalyst synthesized from Parangtritis beach sand is selective for gasoline-fraction hydrocarbon and has hydrocracking activity up to 4 runnings.